2015
DOI: 10.1371/journal.pone.0141960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RXR Agonists on Cell Proliferation/Apoptosis and ACTH Secretion/Pomc Expression

Abstract: Various retinoid X receptor (RXR) agonists have recently been developed, and some of them have shown anti-tumor effects both in vivo and in vitro. However, there has been no report showing the effects of RXR agonists on Cushing’s disease, which is caused by excessive ACTH secretion in a corticotroph tumor of the pituitary gland. Therefore, we examined the effects of synthetic RXR pan-agonists HX630 and PA024 on the proliferation, apoptosis, ACTH secretion, and pro-opiomelanocortin (Pomc) gene expression of mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
(75 reference statements)
1
27
0
Order By: Relevance
“…Interestingly, although POMC is obviously significantly expressed in all specimens, it proved to be overexpressed together with the POMC‐processing co‐adjuvator SCG5 in specimens grouping in cluster B compared to those in clusters A and C. Increased expression of genes involved in other pituitary tumours or ACTH‐secreting neuroendocrine tumours, most notably NOTCH3 , PITX1, LGALS3 and NGRN , was also observed in cluster B. Furthermore, adenomas in this cluster overexpressed the retinoid X receptor beta gene ( RXRB ), thus confirming possibly greater sensitivity to RXR agonists in selected adenomas. TIMP1 (tissue metallopeptidase inhibitor 1) was also overexpressed in cluster B adenomas, which is an interesting result given the recent reports on matrix metalloproteinase‐9 and TIMP1 itself in corticotroph adenomas.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, although POMC is obviously significantly expressed in all specimens, it proved to be overexpressed together with the POMC‐processing co‐adjuvator SCG5 in specimens grouping in cluster B compared to those in clusters A and C. Increased expression of genes involved in other pituitary tumours or ACTH‐secreting neuroendocrine tumours, most notably NOTCH3 , PITX1, LGALS3 and NGRN , was also observed in cluster B. Furthermore, adenomas in this cluster overexpressed the retinoid X receptor beta gene ( RXRB ), thus confirming possibly greater sensitivity to RXR agonists in selected adenomas. TIMP1 (tissue metallopeptidase inhibitor 1) was also overexpressed in cluster B adenomas, which is an interesting result given the recent reports on matrix metalloproteinase‐9 and TIMP1 itself in corticotroph adenomas.…”
Section: Discussionmentioning
confidence: 71%
“…With regard to genes overexpressed in cluster B compared to the other 2 clusters, we observed overexpression of the POMC gene itself, as well as of SCG5 , which encodes for secretogranin 5 (also known as neuroendocrine protein 7B2) associated with prohormone convertase 2 activation . Furthermore, genes involved in neuroendocrine tumours (eg, NOTCH3 , LGALS3, PITX1 and NGRN ) were also overexpressed in cluster B compared to clusters A and C. Additional genes of interest to corticotroph adenoma pathophysiology were RXRB and TIMP1 in view of their links to retinoic acid sensitivity and matrix metalloproteinase, respectively . Given the number of genes overexpressed in this cluster, we could perform functional analysis and detected significant enrichment for 123 genes.…”
Section: Resultsmentioning
confidence: 86%
“…In addition, RXR␣/␤/␥ participates in the induction of cell apoptosis. It has been reported that RXR␣/␤/␥ agonist (retinoic acid) induces apoptosis of tumor cells by activation of both inducible and endothelial nitric-oxide synthase and production of apoptogenic NO (22,23). Because RXR alone and in combination with other nuclear hormone receptors also promotes Th2 differentiation (18), we wondered whether RXR could be exploited to block airway epithelium apoptosis in asthma.…”
mentioning
confidence: 99%
“…In support of this concept, the synthetic RARα/β agonist Am80 up-regulated POMC gene transcription by increasing NeuroD1 and Tpit expression [53] (Table 1). These apparent contradictory actions of RAR activation to either stimulate or inhibit POMC transcription could be explained by involvement of an RXR homodimer or permissive heterodimer that mediates these complex and mixed RXR/RAR actions [54,55].…”
Section: Retinoic Acid Receptors (Rarα Rarβ Rarγ)mentioning
confidence: 99%